Prevalence of Oral Candidiasis in Indian HIV Sero-Positive Patients with CD4(+) Cell Count Correlation - Kirti, Y. K. (Indian J Otolaryngol Head Neck Surg, 2018)
The objective of this study was to investigate the prevalence of oral candidiasis in human immunodeficiency virus/acquired immunodeficiency syndrome patients in India. A descriptive cross-sectional study. To compare the occurrence of candidiasis with the levels of CD4(+) (cluster of differentiation) cell counts. A total of 100 patients infected with HIV were included. Oral lesions were observed, only patients with oral candidiasis were studied and classified. Standard methods were used for collection of oral specimens, culturing and identifying Candida species. Potential correlations between the presence and severity of oral lesions and CD4(+) cells counts were analysed. Candidiasis was detected in 20% of the patients with an mean CD4(+) count being 188. All the patients were on highly active antiretroviral therapy except one. There was pseudomembranous candidiasis in 9, erythematous type in 3, angular chelitis in 2, chronic hyperplastic in 4, and median rhomboid glossitis in 2. Candidiasis is an indicator of low CD4(+) cell count but may be seen at different levels of the disease. In HIV sero-positive patients it is an indicator of falling CD4(+) cell count generally below 200, indicating onset of AIDS. Many a times the patient does not have specific complaints but, it is picked up only on examination. Hence oral cavity examination should be a must in seropositive patients at every clinical follow up.